A COMUNICAÇÃO DA IGREJA CATÓLICA NO BRASIL: tendências comunicacionais da Conferência Nacional dos Bispos do Brasil - ALVARENGA, RICARDO COSTA (2016)
Study about the communication of the Catholic Church in Brazil, with the central objective of identifying the communication trends adopted by the Conferência Nacional dos Bispos do Brasil (CNBB), which is the main structure of power of the Catholic Church in the country, since its creation in 1952. Identifying these communication trends is important, due to the need to systematize the knowledge about the subject and also to contribute to the studies related to the Communication and Religion interface in Brazil. The research was developed based on a bibliographical survey, documentary analysis in CNBB archives, available by the institution‘s Centro de Documentação e Informação, as well as interviews with Church communication leaders, such as bishops, religious and laity who acted as advisors and presidents of the Comissão Episcopal Pastoral para a Comunicação. Our main conclusions are that the Conferência Nacional dos Bispos do Brasil was influenced by social, ecclesial, political and economic aspects to think about the communication and also the figure of the leaders of communication were undoubtedly decisive in certain periods of openness and others of inflection in the relationship of the Church with communication. Their references influenced the work of the conference, as it happened in the early years, which were marked by functionalism and, later, by the critical and social studies